Práctica reflexiva y mejora del área Pedagógico-Didáctica en estudiantes universitarios de formación inicial docente de Educación Primaria, 2021 - Quipuscoa Silvestre, Manuel (2023)
The aim of this study was to improve the Pedagogical-Didactic area of the Preprofessional _x000D_ Practice in the initial teacher training students of the Professional School of Primary _x000D_ Education, through the reflective practice: Action-research, employing McKernan's _x000D_ temporal process model. The participants were a group of students in the final year of initial _x000D_ teacher training. The Digital Field Diary, the reflection questionnaires at the end of the _x000D_ learning sessions, the analytical memos and the satisfaction questionnaire were used for data _x000D_ collection. The data were analysed through the process of coding and categorisation using _x000D_ the QDA Miner software package, as well as information provided by Google Forms. The _x000D_ results show four emerging categories: a) the choice of activities and strategies, b) the _x000D_ organisation of time, c) the interaction with students and d) the use of engaging and _x000D_ innovative resources. Concerning to the development, two emerging categories have been _x000D_ identified: a) motivacional and interactive resources and b) order and children participation. _x000D_ In addition, the reflective practice improved students' satisfaction in relation to the _x000D_ development of the Pedagogical- Didactic area, the support of the classroom teacher and the _x000D_ Head of Preprofessional Practice.